Involvement of Platelet–Tumor Cell Interaction in Immune Evasion. Potential Role of Podocalyxin-Like Protein 1 - Amo, Laura; Tamayo-Orbegozo, Estíbaliz; Maruri, Natalia; Eguizabal, Cristina; Zenarruzabeitia, Olatz; Riñón, Marta; Arrieta, Arantza; Santos, Silvia; Monge, Jorge; Vesga, Miguel Angel; Borrego, Francisco; Larrucea, Susana (Frontiers in Oncology, 2014)
Besides their essential role in hemostasis and thrombosis, platelets are involved in the onset of cancer metastasis by interacting with tumor cells. Platelets release secretory factors that promote tumor growth, angiogenesis, and metastasis. Furthermore, the formation of platelet–tumor cell aggregates in the bloodstream provides cancer cells with an immune escape mechanism by protecting circulating malignant cells from immune-mediated lysis by natural killer (NK) cells. Platelet–tumor cell interaction is accomplished by specific adhesion molecules, including integrins, selectins, and their ligands. Podocalyxin-like protein 1 (PCLP1) is a selectin-ligand protein in which overexpression has been associated with several aggressive cancers. PCLP1 expression enhances cell adherence to platelets in an integrin-dependent process and through the interaction with P-selectin expressed on activated platelets. However, the involvement of PCLP1-induced tumor–platelet interaction in tumor immune evasion still remains unexplored. The identification of selectin ligands involved in the interaction of platelets with tumor cells may provide help for the development of effective therapies to restrain cancer cell dissemination. This article summarizes the current knowledge on molecules that participate in platelet–tumor cell interaction as well as discusses the potential role of PCLP1 as a molecule implicated in tumor immune evasion.